Addressing Rehabilitation Challenges in Long COVID-19 Neurological Complications: Essential Insights from a Follow-up Case Series - Saumya Susan Zacharia; Raji Thomas (Indian Journal of Physical Medicine & Rehabilitation)
Background: There is growing awareness that infection with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) can result in both immediate and prolonged neurological effects. Recognising and diagnosing these neurological complications pose significant challenges and may worsen short- and long-term results, potentially resulting in unfavourable clinical outcomes. Objectives: The objective of the study was to investigate the long-term clinical outcomes and rehabilitation challenges in patients with neurological complications related to COVID-19. Methods: In this case series, we describe the clinical course and outcomes of five male patients aged 18-66 years who developed neurological symptoms after being infected with SARS-CoV-2. Their demographic and clinical data were retrospectively collected from medical records while they underwent rehabilitation at a tertiary care centre. Modified Barthel Index scores and Addenbrooke’s Cognitive Examination (ACE-III) scores at admission and discharge were also collected. A follow-up telephone survey was conducted to assess their quality of life (QoL using WHOQOL-BREF) and long-term clinical and functional status 2 years after discharge from rehabilitation. Results: The patients showed a variety of neurological complications, including stroke, critical illness polyneuropathy, post-viral encephalitis, focal cranial nerve issues and movement disorder but showed significant functional and cognitive recovery, with most achieving full independence in activities of daily living after rehabilitation. Two years post-rehabilitation, long-term improvements were noted in mobility, independence in daily activities, return to work and QoL. However, residual symptoms such as fatigue and motor impairments persisted, highlighting the need for long-term, personalised rehabilitation to address both physical and psychosocial challenges. Conclusion: This case series highlights the neurological complications of post-COVID-19 recovery, emphasising the critical role of rehabilitation in improving patients’ QoL. Effective rehabilitation strategies are essential for managing these complications and aiding recovery.